Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Can anyone help me with the following problem?

Let $W(t), t\geq 0$ be a Brownian motion with filtration:$F(t)$. Let $0\leq s\leq t$.

1- Show that $E\left [ W^{3}(t)\mid F(s) \right ]=W^{3}(s)+3(t-s)W(s)$. where $E\left [ (*)\mid* \right ]$ is the conditional expectation.

2- Show that: $ W^{3}(t)-3\int_{0}^{t}W(u)du$ is a Martingale.

For the First Part: I tried the following: $E\left [ W^{3}(t)\mid F(s) \right ]=E\left [ W^{3}(t)-W^{3}(s)+W^{3}(s) \right ]=E\left [ W^{3}(t)-W^{3}(s) \right ]+E\left [W^{3}(s) \right ]=E\left [ (W(s)-W(t))^{3} +3W(t)W(s)(W(t)-W(s))\right ]+W^{3}(s)=...$

I couldn't move from that point. Can anyone write in detail how I can complete the solution.

For the second part: I did the following $E\left [ W^{3}(t)-3\int_{0}^{t}W(u)du\mid F(s) \right ]=E\left [ W^{3}(t) \mid F(s)\right ]-3E\left [ \int_{0}^{t}W(u)du\mid F(s) \right ]=W^{3}(s)+3(t-s)W(s)-3\int_{0}^{t}E\left [ W(t)\mid F(s) \right ]du$.

Can anyone let me know how to finish my proof?

share|cite|improve this question
What do you know? The definition of conditioning ? Itô's formula? – Did Mar 22 '12 at 6:39
up vote 3 down vote accepted

Note that $W(t)^3=W(s)^3+3W(s)^2V+3W(s)V^2+V^3$ with $V=W(t)-W(s)$. Hence, $\mathrm E(W(t)\mid F(s))=U_3+3U_2+3U_1+U_0$ with $U_i=\mathrm E(W(s)^iV^{3-i}\mid F(s))$.

To compute each $U_i$, one can apply the principle David Williams calls:

Leave out everything that is measurable, integrate everything that is independent.

Here, $W(s)$ is measurable with respect to $F(s)$ and $V$ is independent on $F(s)$ hence $U_i=W(s)^i\mathrm E(V^{3-i})$ for every $i$. Furthermore, the distribution of $V$ is symmetric hence $\mathrm E(V)=\mathrm E(V^3)=0$, and $V$ is gaussian with variance $t-s$ hence $\mathrm E(V^2)=t-s$. Putting everything together, one gets $$ \mathrm E(W(t)\mid F(s))=W(s)^3+3W(s)^2\cdot0+3W(s)\cdot(t-s)+0, $$ that is, $$ \mathrm E(W(t)\mid F(s))=W(s)^3+3(t-s)\cdot W(s). $$ As regards 2., thanks to 1., this reduces to the fact that $$ (t-s)W(s)=\mathrm E\left(X_{s,t}\big\vert F(s)\right),\quad X_{s,t}=\int_s^tW(u)\mathrm du.\tag{E} $$ Do you see why (E) and 1. together imply 2.? Do you see why (E) holds?

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.